CCII and RC fractance based fractional order current integrator. (July 2017) - Goyal, Divya; Varshney, Pragya
Abstract: Integrators are an important functional module of several filters, PID controllers and automated systems. Designing these integrators in fractional domain enhance their operations and make the responses highly precise and accurate. This paper presents a Fractional Order Current Integrator using second generation current conveyor as the active block, and fractional capacitor as a grounded fractance. Analog realization of this fractance comprises of resistances and capacitances arranged in parallel RC ladder topology. The motivation behind this work is that more accurate and stable fractional integrator with fewer passive elements, for lower bias voltage and high dynamic range, can be designed and implemented. Integrators of fractional orders from 0.1 to 0.9 are simulated using TSMC 0.25 µm technology parameters. The transient and frequency responses obtained in Mentor Graphics are in close conformity with the theoretical values of magnitude and phase. Robustness of the proposed model is verified by performing Monte Carlo analysis in time and in frequency domain. Comparisons of fractional order current integrators with existing analog fractance models have also been included to further validate the work presented in the paper.